2007
DOI: 10.2527/jas.2006-560
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dried distillers grains and equivalent undegradable intake protein or ether extract on performance and forage intake of heifers grazing smooth bromegrass pastures1

Abstract: Crossbred heifers (n = 120; BW = 368 kg, SD = 39 kg) were used to determine effects of dried distillers grains (DDG) and relative contributions of undegradable intake protein (UIP) and fat (ether extract, EE) in DDG on ADG and forage intake (FI). Heifers rotationally grazed six 3.5-ha, smooth bromegrass paddocks (IVDMD = 65.7%, CP = 20.8%, UIP = 2.17%, DM basis). Heifers were blocked by previous ADG and allotted to treatments in a 3 × 3 + 1 factorial design. Factors were source and level of supplementation. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 23 publications
12
29
0
Order By: Relevance
“…This increase in weight gain can be attributed to the undegradable intake protein (UIP) and additional energy, from both fat and digestible fiber, provided by the DDGS because pasture in vitro DM digestibility (IVDMDig) did not differ among treatments (P = 0.71; Table 2). This would agree with MacDonald et al (2007) who found that heifers grazing pasture had increased gains when supplemented with distillers grains compared with heifers supplemented with either corn gluten meal or corn oil. Morris et al (2005) reported increased gains of 0.20 kg/d for each kilogram of DDGS supplemented to heifers on a 65% TDN forage diet.…”
Section: Cattle Performancesupporting
confidence: 89%
“…This increase in weight gain can be attributed to the undegradable intake protein (UIP) and additional energy, from both fat and digestible fiber, provided by the DDGS because pasture in vitro DM digestibility (IVDMDig) did not differ among treatments (P = 0.71; Table 2). This would agree with MacDonald et al (2007) who found that heifers grazing pasture had increased gains when supplemented with distillers grains compared with heifers supplemented with either corn gluten meal or corn oil. Morris et al (2005) reported increased gains of 0.20 kg/d for each kilogram of DDGS supplemented to heifers on a 65% TDN forage diet.…”
Section: Cattle Performancesupporting
confidence: 89%
“…This indicates variability in experimental conditions or the CSM itself as supported by Goetsch and Owens (1985). MacDonald et al (2007) obtained CP values of DDGS that support the current study's values, but RUP (51.3%) and TTIDP (57.0%) were lower and RUPDIG (88.8) was higher than in the current study. As demonstrated in this study, RDP (% of DM) in DDGS can be affected by lipid level, and the differences in TTIDP and RUPDIG observed in the current experiment compared with others may be due to variability of DDGS explained by Spiehs et al (2002) and Klopfenstein et al (2008).…”
Section: Resultssupporting
confidence: 76%
“…Of the 10 in situ bags of each sample incubated per steer, 4 were used for determination of RUP (% of CP) and 6 for determination of RUPDIG. One mesh bag containing 40 in situ bags (10 of each ingredient so that every ingredient was incubated in every steer) was placed in the ventral sac of the rumen of each steer and incubated for 16 h. An incubation of 16 h has been commonly used for determination of RUP of concentrate feeds (Kopečný et al, 1998;MacDonald et al, 2007). After incubation, mesh bags were lightly rinsed in water to remove excess ruminal fluid.…”
Section: Rumen Incubations and Mobile Bag Techniquementioning
confidence: 99%
“…A lack of difference in forage disappearance between the 2 double-stocked treatments suggests the DDG did not replace forage. MacDonald et al (2007) found a forage replacement rate of almost 50% when DDG was supplemented to heifers grazing smooth brome pastures at rates ranging from 0.75 to 2.25 kg/d. Extrapolating the finding of MacDonald et al (2007) to the present experiment suggests feeding 2.27 kg/d per animal of DDG would only replace 1.14 kg/d per animal of forage.…”
Section: Resultsmentioning
confidence: 99%
“…However, ethanol production from corn grain has made dried distillers grains (DDG) an available feedstuff that improves growth rate of grazing cattle (Griffin et al, 2012). In addition to demonstrating an increase in animal performance, previous research has demonstrated a substitution effect on forage intake when DDG is fed in forage-based diets (Loy et al, 2007;MacDonald et al, 2007;Griffin et al, 2012). If the cost of DDG is less than the cost of replaced grazed forage on a per unit of energy basis, then cost of production could be decreased by feeding DDG.…”
Section: Introductionmentioning
confidence: 99%